Coping by the Means of Constructing Myths - Kłodkowska, Joanna (INSTED: Interdisciplinary Studies in Education & Society, 2019)
The article is an etnographic study on coping by the means of constructing myths as a strategy used by men who attempt to improve their situation perceived as non-satisfactory or difficult. The opportunity to build practices of coping with the feeling of senselessness of one’s own actions, threatening changes, negative perception of oneself and the world can be, amongst others, fishing. What was discussed and analysed in the text is the meaning of difficult situations and practices of coping with them, as well as coping practices based on constructing the myth about fishing as a story about a constant and meaningful world.